Does social media involvement matter? A scoping review of memorable tourism experience on local food - Sartika; Andriani Kusumawati; Anni Rahimah; Yusri Abdillah (Cogent Social Sciences)
This research seeks to systematically investigates the role of social media in shaping memorable tourism experiences through local food. It evaluates previous studies in this area, highlights existing gaps and limitations, and proposes avenues for further research to enrich knowledge in the field. Utilizing the PRISMA methodology. Articles were identified using keywords such as "memorable tourism experience", "social media", "local food", "culinary", and "digital media". The analysis focused on publications from 2013 to 2023, retrieved from the Scopus and Web of Science databases. The content was reviewed and analyzed using the Publish or Perish software and further processed with Microsoft Excel for content analysis. The analysis highlights that platforms such as Facebook, Instagram, and TikTok are the most utilized for promoting local food and shaping memorable tourism experiences, owing to their visual and interactive features. Conversely, platforms like WeChat and YouTube are less emphasized in this context but still contribute to user engagement and experience-sharing. This scoping review not only identifies gaps and limitations in the existing literature but also provides actionable recommendations for future research and practical applications. It offers a multidimensional framework, contributing to advancing both theoretical and empirical knowledge in digital tourism and culinary tourism.